Dwi Tunggal Pedagogy in Children’s Pesantren: Integrating Teacher–Parent Roles in Relational Islamic Education - Taufikin Taufikin; Sri Nurhayati; Moses Adeleke Adeoye (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This study investigates the mechanism of value internalization in a children’s pesantren through what is conceptualized as Dwi Tunggal Pedagogy—a relational model in which teachers simultaneously enact instructional and parental roles. Rather than broadly examining curriculum or institutional culture, the study specifically analyzes how everyday relational interactions function as the primary socialization process through which moral and spiritual values are internalized by young learners. Using a qualitative case study design, this research was conducted at PPATQ Raudlatul Falah Pati, a Qur’anic boarding school for children aged 7–12. Data were generated through prolonged observation involving 530 students, 123 teachers, and one kiai, as well as in-depth interviews with one kiai, ten teachers (ustadz and ustadzah), ten students, and five parents. Thematic analysis reveals that Dwi Tunggal Pedagogy operates through four interrelated dimensions: relational caregiving, moral–spiritual guidance, emotional attachment, and institutionalized daily interaction. Teachers are not merely transmitters of knowledge but function as consistent attachment figures who provide emotional security, moral discipline, and spiritual nurturing. The findings demonstrate that the effectiveness of children’s pesantren education is deeply rooted in the quality of human relationships rather than instructional structures alone. This study contributes theoretically by extending relational pedagogy and the ethics of care into the context of Islamic boarding education; empirically, by offering rich data from an underexplored setting; and practically, by providing insights for designing child-centered, care-based educational governance in religious boarding schools